Animals through the Prism of Language and Culture - Samardžić, Ana (Poznańskie Studia Slawistyczne, 2021)
The paper is a review which examines the semantic analysis offered in Slobodan Novokmet’s study entitled “Animal Names in Serbian language – Semantic and Linguo-Cultural analysis.” The monograph was published in 2020 by the Institute for the Serbian Language at the Serbian Academy of Sciences and Arts in Belgrade. Although lexicological and lexicographic in its nature, this monograph offers an interdisciplinary approach to the study of animal names in the Serbian language, combining methods of traditional linguistics, i. e. componentional analysis, and the increasingly popular linguocultural approach. The focus of the study is to research the mechanisms of semantic transfer within the meaning of lexems denoting animals, such as metaphor and methonymy. The monograph also deals with the lexicography definitions, offering the ways of their improvement.